Neuronal SIRT1 regulates metabolic and reproductive function and the response to caloric restriction - Rickert, Emily (2018)
Sirt1 is a NAD-dependent class III deacetylase that functions as a cellular energy sensor. In addition to its well-characterized effects in peripheral tissues, emerging evidence suggests that neuronal Sirt1 activity plays a role in the central regulation of energy balance and glucose metabolism. In this study we generated mice expressing an enzymatically inactive form (NMUT) or wild-type SIRT1 (N-OX) in mature neurons. Both N-OX male and female mice showed impaired glucose tolerance, and N-MUT female, but not male, mice showed improvedglucose tolerance compared to WT littermates. Furthermore, all mice showed improved glucose tolerance with caloric restriction (CR), but the N-OX mice showed the greatest change and now showed better glucose tolerance than their littermates. At the reproductive level, N-OX females showed impaired estrous cycles, with increased cycle length and more time in estrus. LH andprogesterone surges were absent on the evening of proestrus in the N-OX mice suggesting a defect in spontaneous ovulation, which was confirmed by the ovarian histology with a reduced number of corpora lutea. Despite this defect, the mice were still fertile when mated to wild-type mice on the day of pro-estrus indicating that the mice can respond to normal pheromonal or environmental cues. When subjected to CR, the N-OX mice went into diestrus arrest earlier than their littermates. Together, these results suggested that the overexpression of SIRT1 rendered the mice more sensitive to the metabolic improvements and suppression of reproductive cycles by CR, which was independent of circadian rhythms.